25.6k views
1 vote
Solve: (step by step please)
x^2+9x+9=0

User Davidsd
by
4.6k points

2 Answers

4 votes

Answer:

X1= -9-3
\sqrt5 over 2 X2= -9+3
\sqrt5 over 2 (draw a line under the -9 to the 5

and put a 2 under like a fraction

i cant get the line all the way

across on here sorry

Step by step explanation:

x= -9
\sqrt9^2 -4x1x9 Over (draw a line under that) Put all that under sq root

2 x 1 also

x= -9+
\sqrt81-36 Over 2

2

x= -9 +
\sqrt45 Over 2

2

x=-9 +3
\sqrt5 Over 2

2

separate solutions gives your answer above

Also ......note ..... put a line under each + sign ok I worked hard getting this all down best i can

User Lisa DeBruine
by
5.3k points
4 votes

Answer:


x=(-9\pm3√(5) )/(2)

Explanation:

Standard Form: ax² + bx + c = 0

Quadratic Formula:
x=(-b\pm√(b^2-4ac) )/(2a)

Step 1: Write equation

x² + 9x + 9 = 0

Since we cannot factor the expression, we will have to use the quadratic formula.

Step 2: Define

a = 1

b = 9

c = 9

Step 3: Solve for x

  1. Substitute:
    x=(-9\pm√(9^2-4(1)(9)) )/(2(1))
  2. Evaluate:
    x=(-9\pm√(81-36) )/(2)
  3. Evaluate:
    x=(-9\pm√(45) )/(2)
  4. Simplify:
    x=(-9\pm3√(5) )/(2)
User Stitz
by
4.9k points